Comparing the emotional impact of the UK COVID-19 lockdown in very preterm and full-term born children: a longitudinal study - Sun, Zeyuan; Hadaya, Laila; Leoni, Marguerite; Dazzan, Paola; Simonoff, Emily; Counsell, Serena J.; Edwards, A. David; Nosarti, Chiara; Vanes, Lucy (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction: The COVID-19 pandemic has caused a global mental health crisis, especially for those individuals who are vulnerable to stress and anxiety due to pre-existing mental health problems. This study aimed to understand the emotional impact of the COVID-19 lockdown on children who were born very preterm (VPT, <32 weeks’ gestation), as they are vulnerable to mental health difficulties and are at increased risk of developing psychiatric problems during childhood compared to their full-term-born counterparts. Methods: The parents of 32 VPT children (mean age=8.7) and 29 term-born controls (mean age=8.8) who had previously taken part in a study of brain development and psychopathology following VPT birth completed an online modified version of the Coronavirus Health and Impact Survey (CRISIS). The emotional impact of the COVID-19 lockdown on the child and the parent, measured by the CRISIS, was studied in relation to pre-existing mental health difficulties, assessed with the parent-rated Strengths and Difficulties Questionnaire (SDQ) evaluated before the CRISIS completion (mean time gap 15 months). T-tests, likelihood ratio F-tests, linear regression models and simple slope analyses were conducted to study the effects of COVID-19-related stressors on children’s and parents’ behavior, relationships and mental health. Results: There were no significant group differences in pre-existing SDQ internalizing/externalizing symptoms, child’s emotions or parent’s emotions during the COVID-19 lockdown. However, higher pre-existing internalizing symptoms in VPT children were associated with greater lockdown-related emotional problems and worries (simple slope=1.95, p<0.001), whereas this was not observed in term-born children. Conclusion: Our results suggest that VPT children with pre-existing internalizing problems may be more vulnerable to the negative impact of certain societal and familial stressors, such as social restrictions during the national COVID-19 lockdown periods. Effective intervention strategies are therefore needed to support this particularly vulnerable group in the context of potentially stressful life changes and adjustments.